2018
DOI: 10.1001/jamaoncol.2018.1977
|View full text |Cite
|
Sign up to set email alerts
|

Association ofMGMTPromoter Methylation Status With Survival Outcomes in Patients With High-Risk Glioma Treated With Radiotherapy and Temozolomide

Abstract: ClinicalTrials.gov Identifier: NCT00114140.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 17 publications
8
110
0
1
Order By: Relevance
“…Most interestingly, we found that SRD5A2 methylation in promoter regions, specifically at CpG# -39 to CpG# -2, is significantly associated with better survival for CRPC patients treated with ADT. Being consistent with the study for high-risk gliomas which showed that MGMT promoter methylation predicts better survival outcomes [30], our finding not only provides evidence that alteration of the epigenome is an important step in cancer progression, but also opens new windows of opportunities in personalized medicine for CRPC patients.…”
Section: Srd5a2 Promoter Methylation Was Negatively Associated With Ssupporting
confidence: 91%
“…Most interestingly, we found that SRD5A2 methylation in promoter regions, specifically at CpG# -39 to CpG# -2, is significantly associated with better survival for CRPC patients treated with ADT. Being consistent with the study for high-risk gliomas which showed that MGMT promoter methylation predicts better survival outcomes [30], our finding not only provides evidence that alteration of the epigenome is an important step in cancer progression, but also opens new windows of opportunities in personalized medicine for CRPC patients.…”
Section: Srd5a2 Promoter Methylation Was Negatively Associated With Ssupporting
confidence: 91%
“…According to Reuss et al ., the characteristic pattern of IDH mutant astrocytic lineage tumors (DA, AA, GBM) is the presence of coexisting loss of nuclear ATRX, and sometimes of strong diffuse nuclear p53 immunostaining. ATRX loss is caused by corresponding gene mutations, while s trong p53 immunostaining in > 10% neoplastic cells is highly correlated with TP53 mutation in diffuse gliomas . In this study, 41% of IDH mutant astrocytomas had no ATRX mutation/protein loss, which is in line with ATRX retention previously found in IDH mutant diffuse gliomas from patients at ≥ 55 years in other studies .…”
Section: Discussionsupporting
confidence: 90%
“…Methylation of the MGMT promoter leads to low expression of MGMT and inactivation of the repair protein, rendering tumor cells more sensitive to effects of alkylating agents [39]. Consequently, MGMT methylation is considered a favorable prognosis marker associated with longer survival outcomes [40].…”
Section: Discussionmentioning
confidence: 99%